2021
DOI: 10.3390/cancers13030483
|View full text |Cite
|
Sign up to set email alerts
|

TFEB Supports Pancreatic Cancer Growth through the Transcriptional Regulation of Glutaminase

Abstract: Transcription factor EB (TFEB) is a master regulator of lysosomal function and autophagy. In addition, TFEB has various physiological roles such as nutrient sensing, cellular stress responses, and immune responses. However, the precise roles of TFEB in pancreatic cancer growth remain unclear. Here, we show that pancreatic cancer cells exhibit a significantly elevated TFEB expression compared with normal tissue samples and that the genetic inhibition of TFEB results in a significant inhibition in both glutamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…We assessed whether MIA shTFEB cells could develop orthotopic tumors to further support the notion that TFEB plays a significant role in PDAC growth. The impact of TFEB knockdown and its family members TFE3 and MITF on PDAC tumor growth has been evaluated in subcutaneous xenografts [ 35 , 37 ], but not in orthotopic models, that better recapitulate human disease. We found that tumors were significantly smaller in MIA shTFEB , than MIA shNT cells, indicating that TFEB contributes to PDAC tumor growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed whether MIA shTFEB cells could develop orthotopic tumors to further support the notion that TFEB plays a significant role in PDAC growth. The impact of TFEB knockdown and its family members TFE3 and MITF on PDAC tumor growth has been evaluated in subcutaneous xenografts [ 35 , 37 ], but not in orthotopic models, that better recapitulate human disease. We found that tumors were significantly smaller in MIA shTFEB , than MIA shNT cells, indicating that TFEB contributes to PDAC tumor growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, TFEB overexpression seems to promote the development of some tumors [ 140 , 141 , 142 ]. Considering this, it is possible that the therapeutic use of TFEB activation may be limited by its oncogenic potential.…”
Section: Lysosomal Opportunities For Intervention In Agingmentioning
confidence: 99%
“…While TFEB-driven autophagy and endolysosomal biogenesis delays aging via the clearance of toxic macromolecules, unremitting activation of TFEB can paradoxically shorten lifespan [ 141 ]. Either the overexpression and/or constitutive nuclear localization of TFEB and TFE3 promote the growth of various types of cancer [ 226 , 227 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. Additionally, amplification of the MITF locus and functional upregulation of MITF are potent drivers of melanoma [ 213 , 241 , 242 , 243 , 244 , 245 , 246 ].…”
Section: Regulation Of Lifespan By Ion Channels Involved In Autophagy...mentioning
confidence: 99%